Contemporary critical theory and methodology - Strydom, Piet, 1946- (Social research today (Routledge (Firm)), 2011)
Contemporary Critical Theory and Methodology is unique in presenting the first critical collection of texts dealing with the debate between critical theory and pragmatism. Piet Strydom focuses in particular on the implications that the relation between the two has for the methodology and research practice of contemporary critical theory.